Wet Steam Flow Ionization and Prospects to Practically Apply Electrical Discharge Devices in Turbo Installations - Tarelin, A.O.; Annopolska, I.Ye. (Проблеми машинобудування, 2019)
This paper considers the experimental studies on steam flow ionization in a supersonic nozzle and possibility of artificial flow ionization influence on unequal-weight processes in the low-pressure cylinder and an increase in turbine efficiency. Results of studies to assess the effect of barrier and corona ionizers on the process of intensifying fine-dispersed wetness in a supersonic nozzle are presented.